STRATEGI PENGEMBANGAN PURI GEDE KABA-KABA SEBAGAI DAYA TARIK WISATA UNGGULAN DESA KABA-KABA KABUPATEN TABANAN, BALI - I Nyoman Sudiarta (Widyadari, 2025)
Puri Gede Kaba-Kaba is one of the cultural tourism objects located in Kaba-Kaba Village, Kediri District, Tabanan Regency, Bali Province. This palace is used as a tourist attraction because the building has traditional Balinese architectural art, as well as the application of the Sanga Mandala and Asta Kosala Kosali concepts that are still preserved until now. In addition, activities at the location still reflect the strong Balinese culture supported by a cool environment with a very wide expanse of rice fields and close to other famous tourist attractions such as Tanah Lot and Nyanyi Tabanan Beach. Tourists can do various things at Puri Gede Kaba-Kaba such as participating in the tour of the palace, taking pictures and enjoying traditional dishes. Tourists can also tour Kaba-Kaba Village by bicycle or walking along the cool rice fields and beautiful scenery. Data analysis techniques are carried out qualitatively descriptive and SWOT analysis. Based on the results of the analysis, it was concluded that Puri Gede Kaba-Kaba is in Quadrant V, which means maintaining and preserving (unchanged strategy) to continue to be developed as a leading cultural tourism object in Tabanan Regency. The development of cultural attractions with the existence of Puri Gede Kaba-Kaba must be linked to various other tourism activities, both in Kaba-Kaba Village and other famous tourist attractions close to Puri Kaba-Kaba. The development of cultural tourism attractions is not only from Puri Gede Kaba-Kaba itself but also the environment around Kaba-Kaba Village in general